THE INFLUENCE OF COLLABORATIVE GOVERNANCE AND COORDINATION ON ORGANIZATIONAL PERFORMANCE IN THE PROCESS OF INFRASTRUCTURE DEVELOPMENT FOR ECONOMIC EMPOWERMENT IN THE CITY OF BEKASI - Benyamin Haritz; Lia Muliawaty (Universitas Pasundan, 2020)
The main problem in this research is the performance of organizations in infrastructure development for economic empowerment in Bekasi City has not increased which is assumed by Collaborative Governance and coordination that has not been implemented effectively. The research method used was an explanatory survey method with a quantitative approach. Research shows that collaborative governance and coordination to simultaneously deliver a huge influence (86, 2 %) and significant impact on the performance of the organization in the development of infrastructure in the public interest in Bekasi. Organizations on the development of infrastructure in the public interest in Bekasi was not only influenced by collaborative governance and coordination alone but there are other variables that come to influence the amount of (13, 8 %). Partially Collaborative governance in the process of infrastructure development provides the smallest and most significant influence on the performance of organizations in infrastructure development for the economic empowerment to public interest in the City of Bekasi compared to coordination of 34 , 3 %. The dimensions of the Collaborative governance that provide the most impact to the smallest of the performance of the organization in order are the dimensions of the system contexts (13, 7 %), drivers (9.3%) and dimensional dynamics collaboration (4.0%).Partially the coordination in the process of infrastructure development has the most significant and significant influence on the performance of organizations in infrastructure development for the public interest in Bekasi City